2013
DOI: 10.1007/s00403-013-1416-8
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase enzymes in skin fibrosis: molecular targets and therapeutic agents

Abstract: Fibrosis is characterized by the excessive deposition of extracellular matrix components eventually resulting in organ dysfunction and failure. In dermatology, fibrosis is the hallmark component of many skin diseases, including systemic sclerosis, graft versus host disease, hypertrophic scars, keloids, nephrogenic systemic fibrosis, porphyria cutanea tarda, restrictive dermopathy and other conditions. Fibrotic skin disorders may be debilitating and impair quality of life. There are few FDA-approved anti-fibrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 119 publications
(208 reference statements)
1
24
0
Order By: Relevance
“…Oxidative stress and NOX have been implicated in several skin diseases, especially fibrotic diseases (Wan and Evans, ; De Felice et al , ; Wagner et al , ; Babalola et al , ; Grygiel‐Gorniak and Puszczewicz, ). NOX4 has been proposed as a potential target for systemic sclerosis (scleroderma) (Dooley et al , ; Bohm et al , ; Spadoni et al , ).…”
Section: Diseases By Organmentioning
confidence: 99%
“…Oxidative stress and NOX have been implicated in several skin diseases, especially fibrotic diseases (Wan and Evans, ; De Felice et al , ; Wagner et al , ; Babalola et al , ; Grygiel‐Gorniak and Puszczewicz, ). NOX4 has been proposed as a potential target for systemic sclerosis (scleroderma) (Dooley et al , ; Bohm et al , ; Spadoni et al , ).…”
Section: Diseases By Organmentioning
confidence: 99%
“…NOX-derived ROS have been identified as the main source of oxidative stress, which promotes key events in the development of fibrotic diseases (such as skin fibrosis [9], idiopathic pulmonary fibrosis [10], liver fibrosis [11], and kidney fibrosis [12]) as well as the initiation and progression of cancer [13]. To date, there is no cure for most of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent studies have indicated that the NOX1/4 dual inhibitor GKT137831 can significantly inhibit the activation of HSCs and the development of liver fibrosis. 12 , 66 68 This inhibitor is currently being investigated in Phase II clinical trials. Therefore, NOX-targeting drugs with low toxicity that are effective against fibrosis are expected to lead to a breakthrough in the treatment of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%